Designing Museum and Plaza in Brebes as a City Icon - Putri , Sukma Rizki Cahyaning; Prasetya, L Edhi (Journal of Aesthetics, Creativity and Art Management, 2024)
This research aims to address the lack of facilities supporting arts and culture in Brebes, Central Java, Indonesia, while maximizing its economic and cultural potential. It proposes the design idea of a museum building and a public park as an icon in Brebes Regency, aiming to create an integrated zone for artistic and community economic activities that will enhance the new face of the city. The research methodology involves searching for design ideas by identifying existing problems around the location, which serve as the foundation for designing a building that can accommodate cultural diversity and serve as a space for street vendors within a well-organized zone. Through a contemporary architectural theme inspired by the unique cultural blend of Brebes, the project envisions not only a space for preserving and educating about local culture but also a center for economic activities, ultimately contributing to the socio-economic development of Brebes Regency. The Museum and People's Park serves as a means of development and education of culture and art. It is a solution to the problems that exist, especially for street vendors. The implications of the design concept of the museum building and public park serve as an economic driver for Brebes and will become a new landmark for the city on the northern coast of Java.